2020
DOI: 10.1177/0958305x20907081
|View full text |Cite
|
Sign up to set email alerts
|

Spillover effects between energies, gold, and stock: the United States versus China

Abstract: This study investigates the time–frequency dynamics of return and volatility spillovers between the stock market and three commodity markets: natural gas, crude oil, and gold via a comparative analysis between the United States and China is conducted with the help of new empirical methods. Our findings are as follows. First, in terms of time, return spillovers between crude oil and the stock market are strongest in two of the three commodity markets. Crude oil emits a net negative return spillover to the US st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 48 publications
4
17
0
Order By: Relevance
“…The return spillovers from all energy markets and financial variables to renewable energy stocks in both the US and Europe increased steadily during the 2008 global financial crisis and reached a peak during the European debt crisis. This result supports the view that a link between the commodity and financial markets would increase during periods of financial turmoil [41,42]. According to Ferrer et al [19], we can interpret the increased spillover via uncertainty.…”
Section: Time-varying Spillover Analysissupporting
confidence: 84%
See 2 more Smart Citations
“…The return spillovers from all energy markets and financial variables to renewable energy stocks in both the US and Europe increased steadily during the 2008 global financial crisis and reached a peak during the European debt crisis. This result supports the view that a link between the commodity and financial markets would increase during periods of financial turmoil [41,42]. According to Ferrer et al [19], we can interpret the increased spillover via uncertainty.…”
Section: Time-varying Spillover Analysissupporting
confidence: 84%
“…Thereafter, the return spillovers to renewable energy stocks in both regions increased drastically after 2015 and 2018 because of the OPEC's 2014 announcement that it would maintain production despite declining prices, and the China-US trade war, which led to stock and bond market instability from 2018. He et al [41] and Bhardwaj et al [42] also stated that the links between commodity and financial markets would increase during periods of financial turmoil. A plausible explanation is that market participants review and process any positive or negative information more thoroughly during a period of high uncertainty, thus stimulating an increase in spillovers to renewable energy stocks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bouri (2015) also revealed the entire period exposes low unidirectional transmissions of return and volatilities from oil to the stock market. He et al (2020) found the greatest return spillovers between the oil and stock market. Crude oil has a negative spillover return to the stock market, while the stock market has a positive spillover return.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 98%
“…He stated that oil prices negatively affect the exchange rate, and the equity market affects the exchange rate. He et al (2020) proved gold has a positive and negative spillover in both the USA and China's stock market, respectively. Malik and Hammoudeh (2007) confirmed volatility and spillover studies have an excellent effect on asset pricing, portfolio managers, oil price, and equity.…”
Section: Introductionmentioning
confidence: 99%